Using Single-Case Designs in Practical Settings: Is Within-Subject Replication Always Necessary? - Lanovaz, Marc J.; Turgeon, Stéphanie; Cardinal, Patrick; Wheatley, Tara L. (Perspectives on behavior science, 2019)
Behavior analysts have widely adopted and embraced within-subject replication through the use of reversal and multielement designs. However, the withdrawal of treatment, which is central to these designs, may not be desirable, feasible, or even ethical in practical settings. To examine this issue, we extracted 501 ABAB graphs from theses and dissertations to examine to what extent we would have reached correct or incorrect conclusions if we had based our analysis on the initial AB component only. In our first experiment, we examined the proportion of datasets for which the results of the first AB component matched the results of the subsequent phase reversals. In our second experiment, we calculated three effect size estimates for the same datasets to examine whether these measures could predict the relevance of conducting a within-subject replication. Our analyses indicated that the initial effects were successfully replicated at least once in approximately 85% of the cases and that effect size may predict the probability of within-subject replication. Overall, our results support the rather controversial proposition that it may be possible to set threshold values of effect size above which conducting a replication could be considered unnecessary. That said, more research is needed to confirm and examine the generalizability of these results prior to recommending changes in practice.